Penerapan Biopori dan Rain Barrel Dalam Reduksi Limpasan Air Hujan di Perumahan Sumbersari Permai 2 Kecamatan Sumbersari - Muhammad Alfin Alawy Al Maliki (Fakultas Teknik, 2026)
Sumbersari District receives relatively high and fluctuating annual rainfall. The peak occurs between December and February. Population growth in this area is the highest in Jember Regency from 2020 to 2024. This has driven land conversion into residential areas, reducing infiltration areas and increasing the potential for surface runoff. The Sumbersari Permai 2 housing complex is vulnerable to flooding during heavy rains because rainwater management still relies solely on existing drainage channels without additional runoff reduction measures. This study aims to assess the condition and dimensions of existing drainage channels, calculate rainwater runoff discharge, and evaluate the effectiveness of Biopore Infiltration Holes (LRB) and rain barrels in reducing runoff. This study combines primary and secondary data. Primary data includes channel dimensions and elevations measured by Real Time Kinematic (RTK) surveys and soil infiltration rates from double-ring infiltrometer tests. Secondary data consists of twenty years of rainfall records, land use maps, and supporting literature. Design rainfall was determined using a Log Pearson Type III distribution, then used to hydraulically model the existing drainage system with EPA SWMM. The scenarios used were, LRB, and rain barrels individually and combined. The results showed that the drainage network consisted of closed and open channels with two outlets, resulting in a peak runoff discharge of 1,386.44 m³/s without LID . The LRB scenario reduced the discharge to 1.38487 m³/s (0.63% volume reduction); the 200-liter rainwater harvesting barrel reduced the discharge to 1.38544 m³/s (0.27% height reduction, 0.25% volume reduction). The combined scenario of LRB and rain barrels achieved the highest reduction: 1.52% in height and 0.88% in volume. The study concluded that although land limitations limit the effectiveness of individual LID, combining LID approaches is crucial for more optimal and sustainable stormwater management.
:: Finalisasi file repositori 4 Agustus 2026_Kurnadi
Keywords: drainage; rainwater runoff; biopori infiltration well; rain barrel; Low Impact Development; EPA SWMM